Towards a comprehensive analysis of agricultural land systems: What can we see with publicly available datasets in the EU and US? - Emily Burchfield; Marco Ferro; Silke Hüttel; Tobia Maike Lakes; Heidi Leonhardt; Andreas Niedermayr; Andrea Rissing; Stefan Seifert; Maximilian Wesemeyer (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2024)
Understanding agricultural land systems is paramount to preparing for future transitions under climate change. A first step in moving towards a systematic, multi-context comparison of agricultural land systems is an assessment of data availability and commensurability. We compare publicly available and publicly curated data describing agricultural land systems-those devoted to the production of food, fuel, and fiber-to map analytical potential for comparative research in the United States (US) and European Union (EU). We discuss how political priorities shape what we can(not) see in each region and articulate future data needs to support cross-context understanding of agricultural land systems dynamics. This comprehensive understanding of how and why agricultural land systems change is imperative to promoting sustainable, resilient, and just agriculture futures.
urn:nbn:de:kobv:11-110-18452/29262-2
Keywords: 330; land systems; agricultural land; data comparison; US Farm Bill; EU Common Agricultural Policy